A kind of low-density nylon and preparation method thereof

By introducing specific enhancement additives in the preparation of nylon, the problem of poor performance of low-density nylon in the prior art is solved, and the effect of improving the cross-linking degree and strength of nylon is achieved.

CN116082835BActive Publication Date: 2025-04-01ZHENGZHOU HOLLOWLITE MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310164068.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-04-01
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

While reducing the density of nylon, it is difficult to improve its crosslinking degree and strength, resulting in poor performance of the prepared low-density nylon.

Method used

By adding specific enhancement additives, small hydroxy acid molecules react with trifunctional isocyanate to prepare enhancement additives, and mix them with PA66, talc powder, glass microbeads and other materials during the preparation of nylon, and extrude them at specific temperatures and pressures using a twin-screw extruder to improve the crosslinking and strength of nylon.

Benefits of technology

The cross-linking degree and strength of nylon are improved on the basis of reducing density, and the obtained low-density nylon has higher strength and improved performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004095273480000071
    Figure BDA0004095273480000071
Patent Text Reader

Abstract

The present invention provides a low-density nylon and a preparation method thereof; the preparation method comprises the following steps: a) dissolving a hydroxy acid small molecule in a solvent, cooling after removing water, adding a trifunctional isocyanate to react for 1h to 2h, then adding a catalyst to continue reacting for 3h to 5h under the protection of an inert gas and stirring, and obtaining a reinforcing agent; b) mixing PA66, talcum powder, glass microbeads, the reinforcing agent obtained in step a) and a silane coupling agent, and extruding with a twin-screw extruder at 275°C to 295°C and vacuuming to ‑0.08MPa to ‑0.05MPa to obtain a low-density nylon. Compared with the prior art, the preparation method provided by the present invention selects specific raw materials, especially introduces specific reinforcing agents, cooperates with specific preparation processes, conditions and parameters, realizes overall better interaction, and the obtained low-density nylon has higher strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nylon products, and more specifically to a low-density nylon and a preparation method thereof. Background Art

[0002] Polyamide, commonly known as nylon, is a general term for thermoplastic resins containing repeating amide groups -[NHCO]- on the main chain of the molecule, including aliphatic PA, aliphatic-aromatic PA and aromatic PA. Among them, aliphatic PA has many varieties, large output and wide application. Its name is determined by the specific number of carbon atoms in the synthetic monomer.

[0003] PA is widely used in daily life due to its good mechanical properties and easy processing. At present, low-density nylon is needed in some fields. The existing technology generally adds glass microspheres to reduce density. Glass microspheres have the characteristics of low density and high strength. They are widely used in adhesives, coatings, plastic modification, etc. to reduce density and improve thermal insulation performance; however, when glass microspheres are used in nylon plastics, since their surface does not contain functional groups that can react with the matrix, their microscopic surface bonding force is relatively poor, which makes the prepared plastic performance relatively poor. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a low-density nylon and a preparation method thereof. The preparation method provided by the present invention achieves an increase in the degree of crosslinking while reducing the density by adding a specific reinforcing additive, thereby obtaining a low-density and high-strength nylon product.

[0005] The present invention provides a method for preparing low-density nylon, comprising the following steps:

[0006] a) dissolving a hydroxy acid small molecule in a solvent, removing water and cooling, then adding a trifunctional isocyanate to react for 1 h to 2 h, and then adding a catalyst to continue the reaction for 3 h to 5 h under the protection of an inert gas and stirring to obtain a reinforcing agent;

[0007] b) PA66, talcum powder, glass beads, the reinforcing agent obtained in step a) and the silane coupling agent are mixed and then extruded using a twin-screw extruder at 275° C. to 295° C. and vacuumed to -0.08 MPa to -0.05 MPa to obtain low-density nylon.

[0008] Preferably, the hydroxy acid small molecule in step a) is selected from one or more of 2-hydroxypropionic acid, γ-hydroxybutyric acid and hydroxysuccinic acid.

[0009] Preferably, the solvent in step a) is selected from dimethylformamide and / or dimethyl sulfoxide.

[0010] Preferably, the temperature of dehydration in step a) is 110°C to 120°C, and the time is 2h to 3h; and the temperature of cooling is 70°C to 80°C.

[0011] Preferably, the trifunctional isocyanate in step a) is selected from one or more of HDI biuret, HDI trimer, TDI trimer and IPDI trimer.

[0012] Preferably, the catalyst in step a) is selected from dibutyltin dilaurate and / or dibutyltin dichloride.

[0013] Preferably, the molar ratio of the hydroxy acid small molecule to the trifunctional isocyanate in step a) is (2.9-3.1):1;

[0014] The amount of the solvent used is 50% to 100% of the total mass of the hydroxy acid small molecules and the trifunctional isocyanate;

[0015] The amount of the catalyst used is 0.0003 to 0.001 of the total mass of the hydroxy acid small molecules and the trifunctional isocyanate.

[0016] Preferably, the stirring speed in step a) is 40 r / min to 60 r / min.

[0017] Preferably, the mass ratio of PA66, talcum powder, glass beads, the reinforcing agent obtained in step a) and the silane coupling agent in step b) is (50-80): (10-30): (5-20): (5-10): (0.5-1).

[0018] The present invention also provides a low-density nylon, which is prepared by the preparation method described in the above technical solution.

[0019] The present invention provides a low-density nylon and a preparation method thereof; the preparation method comprises the following steps: a) dissolving a hydroxy acid small molecule in a solvent, removing water and cooling, then adding a trifunctional isocyanate to react for 1h to 2h, then adding a catalyst under inert gas protection and stirring to continue reacting for 3h to 5h to obtain a reinforcing agent; b) mixing PA66, talcum powder, glass microbeads, the reinforcing agent obtained in step a) and a silane coupling agent, and extruding with a twin-screw extruder at 275°C to 295°C and vacuuming to -0.08MPa to -0.05MPa to obtain a low-density nylon. Compared with the prior art, the preparation method provided by the present invention selects specific raw materials, especially introduces specific reinforcing agents, cooperates with specific preparation processes, conditions and parameters, achieves overall better interaction, and the obtained low-density nylon has higher strength.

[0020] At the same time, the preparation method provided by the present invention has simple process, mild conditions, easy control, and broad application prospects. DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The present invention provides a method for preparing low-density nylon, comprising the following steps:

[0023] a) dissolving a hydroxy acid small molecule in a solvent, removing water and cooling, then adding a trifunctional isocyanate to react for 1 h to 2 h, and then adding a catalyst to continue the reaction for 3 h to 5 h under the protection of an inert gas and stirring to obtain a reinforcing agent;

[0024] b) PA66, talcum powder, glass beads, the reinforcing agent obtained in step a) and the silane coupling agent are mixed and then extruded using a twin-screw extruder at 275° C. to 295° C. and vacuumed to -0.08 MPa to -0.05 MPa to obtain low-density nylon.

[0025] The present invention firstly dissolves the hydroxy acid small molecules in a solvent, removes water and cools down, then adds trifunctional isocyanate to react for 1h to 2h, then adds a catalyst under the protection of an inert gas and stirs to continue the reaction for 3h to 5h (preferably 3h to 4h) to obtain a reinforcing agent.

[0026] In the present invention, the hydroxy acid small molecule is preferably selected from one or more of 2-hydroxypropionic acid, γ-hydroxybutyric acid and hydroxysuccinic acid, more preferably 2-hydroxypropionic acid, γ-hydroxybutyric acid or hydroxysuccinic acid. The present invention has no particular restrictions on the source of the hydroxy acid small molecule, and commercially available products known to those skilled in the art can be used.

[0027] In the present invention, the solvent is preferably selected from dimethylformamide and / or dimethyl sulfoxide, more preferably dimethylformamide or dimethyl sulfoxide. The present invention has no particular limitation on the source of the solvent, and commercially available products known to those skilled in the art can be used.

[0028] In the present invention, the temperature of the water removal is preferably 110° C. to 120° C., more preferably 110° C. to 115° C., and the time is preferably 2 h to 3 h, more preferably 2 h to 2.5 h.

[0029] In the present invention, the cooling temperature is preferably 70° C. to 80° C., which is the temperature of the subsequent reaction.

[0030] In the present invention, the trifunctional isocyanate is preferably selected from one or more of HDI biuret, HDI trimer, TDI trimer and IPDI trimer, and more preferably HDI biuret, HDI trimer or IPDI trimer. The present invention has no particular restriction on the source of the trifunctional isocyanate, and commercially available products well known to those skilled in the art can be used.

[0031] In the present invention, the catalyst is preferably selected from dibutyltin dilaurate and / or dibutyltin dichloride, more preferably dibutyltin dilaurate or dibutyltin dichloride. The present invention has no particular limitation on the source of the catalyst, and commercially available products known to those skilled in the art can be used.

[0032] In the present invention, the molar ratio of the hydroxy acid small molecule to the trifunctional isocyanate is preferably (2.9-3.1):1, more preferably 3:1.

[0033] In the present invention, the amount of the solvent is preferably 50% to 100% of the total mass of the hydroxy acid small molecules and the trifunctional isocyanate, and more preferably 90% to 100%.

[0034] In the present invention, the amount of the catalyst is preferably 0.0003 to 0.001 (0.3 ten thousandths to 0.1 thousandths) of the total mass of the hydroxy acid small molecules and the trifunctional isocyanate, and more preferably 0.0003 to 0.0005.

[0035] In the present invention, the inert gas is preferably nitrogen.

[0036] In the present invention, the stirring speed is preferably 40 r / min to 60 r / min.

[0037] After obtaining the reinforcing agent, the present invention mixes PA66, talcum powder, glass beads, reinforcing agent and silane coupling agent, and extrude them using a twin-screw extruder at 275° C. to 295° C. (preferably 280° C. to 290° C.) and vacuuming to -0.08 MPa to -0.05 MPa (preferably -0.06 MPa to -0.055 MPa) to obtain low-density nylon.

[0038] The present invention has no special restrictions on the sources of the PA66, talcum powder, glass microbeads and silane coupling agent, and commercially available products known to those skilled in the art may be used.

[0039] In the present invention, the silane coupling agent is preferably selected from one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, aminopropyltrimethoxysilane and aminopropyltriethoxysilane, more preferably γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane or aminopropyltrimethoxysilane.

[0040] In the present invention, the mass ratio of the PA66, talc, glass beads, the reinforcing agent obtained in step a) and the silane coupling agent is preferably (50-80): (10-30): (5-20): (5-10): (0.5-1), and more preferably (70-80): (20-25): (5-15): (6-8): (0.5-0.8).

[0041] In order to make the nylon product have better strength, the present invention first synthesizes a reinforcing auxiliary agent, the molecular chain of which contains at least 2.8 functional carboxyl groups that can react with nylon, and then can react with the nylon matrix when preparing the nylon product to increase its crosslinking degree, thereby increasing its strength.

[0042] The present invention also provides a low-density nylon, which is prepared by the preparation method described in the above technical solution. In the present invention, the nylon product without adding the reinforcing auxiliary agent prepared by the method has a linear structure and relatively low strength. The present invention first prepares a reinforcing auxiliary agent that can increase the crosslinking degree of nylon to improve its strength. First, a trifunctional isocyanate is reacted with a hydroxy acid to prepare a small molecule containing at least 2.8 carboxyl groups, which is prepared into a modified substance. Then, when preparing the nylon material, the modified substance is used to increase its crosslinking degree, and finally a low-density nylon product with higher strength is obtained.

[0043] The present invention provides a low-density nylon and a preparation method thereof; the preparation method comprises the following steps: a) dissolving a hydroxy acid small molecule in a solvent, removing water and cooling, then adding a trifunctional isocyanate to react for 1h to 2h, then adding a catalyst under inert gas protection and stirring to continue reacting for 3h to 5h to obtain a reinforcing agent; b) mixing PA66, talcum powder, glass microbeads, the reinforcing agent obtained in step a) and a silane coupling agent, and extruding with a twin-screw extruder at 275°C to 295°C and vacuuming to -0.08MPa to -0.05MPa to obtain a low-density nylon. Compared with the prior art, the preparation method provided by the present invention selects specific raw materials, especially introduces specific reinforcing agents, cooperates with specific preparation processes, conditions and parameters, achieves overall better interaction, and the obtained low-density nylon has higher strength.

[0044] At the same time, the preparation method provided by the present invention has simple process, mild conditions, easy control, and broad application prospects.

[0045] In order to further illustrate the present invention, the following examples are used to explain it in detail. The raw materials used in the following examples and comparative examples of the present invention are all commercially available; among them, the glass microspheres used are produced by Zhengzhou Shenglait Hollow Microsphere New Material Co., Ltd., with a D90 of 15μm to 40μm and a true density of 0.4g / cm 3 ~0.7g / cm3 of hollow microbeads.

[0046] Example 1

[0047] (1) Synthesis of reinforcing agent: HDI biuret and 2-hydroxypropionic acid in a molar ratio of 1:3 are used as reaction raw materials, dibutyltin disilicate with a total mass of 0.0003 of the above reaction raw materials is used as a catalyst, and dimethylformamide with a total mass of 100% of the above reaction raw materials is used as a solvent; firstly, the hydroxy acid small molecule 2-hydroxypropionic acid is dissolved in the solvent, and water is removed at 110°C for 2 hours, then the temperature is lowered to 75°C, and trifunctional isocyanate HDI biuret is added to react for 2 hours, and then under nitrogen protection, the catalyst is added and the reaction is continued for 3 hours while stirring at 60r / min to obtain the reinforcing agent.

[0048] (2) 70 parts by weight of PA66, 20 parts by weight of talc, 8 parts by weight of glass microspheres HS70, 8 parts by weight of the reinforcing agent obtained in step (1), and 0.5 parts by weight of silane coupling agent γ-glycidyloxypropyltrimethoxysilane are mixed uniformly, and then a twin-screw extruder is used to extrude at 280° C. and vacuum to -0.06 MPa to obtain a low-density nylon product.

[0049] Example 2

[0050] (1) Synthesis of reinforcing agent: HDI trimer and γ-hydroxybutyric acid in a molar ratio of 1:3 are used as reaction raw materials, dibutyltin dichloride (0.0004 of the total mass of the above reaction raw materials) is used as a catalyst, and dimethyl sulfoxide (90% of the total mass of the above reaction raw materials) is used as a solvent; firstly, the hydroxy acid small molecule γ-hydroxybutyric acid is dissolved in the solvent, and water is removed at 115°C for 2.5 hours, then the temperature is lowered to 70°C, and trifunctional isocyanate HDI trimer is added to react for 2 hours, and then under nitrogen protection, the catalyst is added and the reaction is continued for 4 hours while stirring at 40r / min to obtain the reinforcing agent.

[0051] (2) 80 parts by weight of PA66, 25 parts by weight of talc, 6 parts by weight of glass microspheres HS60, 6 parts by weight of the reinforcing agent obtained in step (1), and 0.8 parts by weight of a silane coupling agent γ-glycidyloxypropyltriethoxysilane are mixed uniformly, and then a twin-screw extruder is used to extrude at 280° C. and vacuum to -0.055 MPa to obtain a low-density nylon product.

[0052] Example 3

[0053] (1) Synthesis of reinforcing agent: IPDI trimer and hydroxysuccinic acid in a molar ratio of 1:3 are used as reaction raw materials, dibutyltin disilicate (0.0005 of the total mass of the above reaction raw materials) is used as a catalyst, and dimethylformamide (100% of the total mass of the above reaction raw materials) is used as a solvent; firstly, the hydroxy acid small molecule hydroxysuccinic acid is dissolved in the solvent, and water is removed at 110°C for 2 hours, then the temperature is lowered to 80°C, and trifunctional isocyanate IPDI trimer is added to react for 1 hour, and then under nitrogen protection, the catalyst is added and the reaction is continued for 4 hours while stirring at 60 r / min to obtain the reinforcing agent.

[0054] (2) 75 parts by weight of PA66, 20 parts by weight of talc, 5 parts by weight of glass microspheres HS42, 8 parts by weight of the reinforcing agent obtained in step (1), and 0.8 parts by weight of a silane coupling agent aminopropyltrimethoxysilane are mixed uniformly, and then extruded using a twin-screw extruder at 290° C. and vacuumed to -0.06 MPa to obtain a low-density nylon product.

[0055] Comparative Example 1

[0056] The preparation method provided in Example 1 is adopted, except that the reinforcing auxiliary agent obtained in step (1) is not added; and a nylon product is obtained.

[0057] Comparative Example 2

[0058] The preparation method provided in Example 2 is adopted, except that the reinforcing auxiliary agent obtained in step (1) is not added; and a nylon product is obtained.

[0059] Comparative Example 3

[0060] The preparation method provided in Example 3 is adopted, except that the reinforcing auxiliary agent obtained in step (1) is not added; and a nylon product is obtained.

[0061] Various performance tests were performed on the products obtained in Examples 1 to 3 and Comparative Examples 1 to 3. The test results are shown in Table 1.

[0062] Sample testing: The density of the embodiments and comparative examples was tested by the drainage method. The samples of the embodiments and comparative examples were prepared into standard dumbbell-shaped specimens of 16.5 cm × 1.0 cm × 0.4 cm using an injection molding machine. The specimens were cured for 7 days at 23°C × 50% relative humidity. The mechanical properties were tested using a universal tensile testing machine at a speed of 10 mm / min.

[0063] Table 1 Performance data of the products obtained in Examples 1 to 3 and Comparative Examples 1 to 3

[0064]

[0065] As can be seen from Table 1, Examples 1 to 3 of the present invention introduce carboxyl groups that can react with nylon when preparing nylon products by preparing specific reinforcing additives, thereby increasing the crosslinking degree of the nylon products and improving their ultimate strength; the present invention can increase the mechanical properties of plastics by more than 10% by introducing reinforcing additives.

[0066] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing low-density nylon, comprising the following steps: a) dissolving a hydroxy acid small molecule in a solvent, removing water and cooling, then adding a trifunctional isocyanate to react for 1h to 2h, then adding a catalyst to continue the reaction for 3h to 5h under the protection of an inert gas and stirring, to obtain a reinforcing agent; the hydroxy acid small molecule is selected from one or more of 2-hydroxypropionic acid, γ-hydroxybutyric acid and hydroxysuccinic acid; the trifunctional isocyanate is selected from one or more of HDI biuret, HDI trimer, TDI trimer and IPDI trimer; the molar ratio of the hydroxy acid small molecule to the trifunctional isocyanate is (2.9 to 3.1): 1; the amount of the solvent is 50% to 100% of the total mass of the hydroxy acid small molecule and the trifunctional isocyanate; the amount of the catalyst is 0.0003 to 0.001 of the total mass of the hydroxy acid small molecule and the trifunctional isocyanate; b) mixing PA66, talcum powder, glass microspheres, the reinforcing agent obtained in step a) and a silane coupling agent, and extruding the mixture using a twin-screw extruder at 275° C. to 295° C. and under vacuum to -0.08 MPa to -0.05 MPa to obtain low-density nylon; the mass ratio of PA66, talcum powder, glass microspheres, the reinforcing agent obtained in step a) and the silane coupling agent is (50 to 80): (10 to 30): (5 to 20): (5 to 10): (0.5 to 1).

2. The preparation method according to claim 1, characterized in that: In step a), the solvent is selected from dimethylformamide and / or dimethyl sulfoxide.

3. The preparation method according to claim 1, characterized in that: The temperature of dehydration in step a) is 110°C to 120°C, and the time is 2h to 3h; the temperature of cooling is 70°C to 80°C.

4. The preparation method according to claim 1, characterized in that: The catalyst in step a) is selected from dibutyltin dilaurate and / or dibutyltin dichloride.

5. The preparation method according to claim 1, characterized in that: The stirring speed in step a) is 40 r / min to 60 r / min.

6. A low-density nylon, characterized in that: The preparation method is described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-strength breathable composite material

    CN108727763A